Correction of Anemia and Evaluation of Efficacy of Red Blood Cell Transfusion in Patients with Oncohematological Diseases - NA Romanenko; AV Chechetkin; LYu Zhiguleva; GV Grishina; SV Bondarchuk; SS Bessmel’tsev (Клиническая онкогематология)
Aim. To study the quality of life (QL) of patients with oncohematological diseases and anemia with respect to hemoglobin level and to evaluate the efficacy of red blood cell transfusion (RBCT).